The association between counselor ratings of working alliance and in-session empathy among sex offender counselors - Carrola, Paul A. (Journal of addictions & offender counseling, 2024)
Factors such as the therapeutic relationship and working alliance have been shown to be important predictors for client outcomes in broad counseling settings with diverse client populations. The present study used linear multiple regression analysis to explore how relational factors such as in-session empathy and mindfulness impact working alliance when providing sex offender counseling. Results from sex offender counselor participants (N = 109) showed that the perspective taking aspect of empathy was most impactful on working alliance and that in-session mindfulness was less impactful on working alliance.